Equality under Threat by the Talented: Evidence from Worker-Managed Firms - Gabriel Burdín (Institute for the Study of Labor (IZA), 2013)
Are high-ability individuals more likely to quit egalitarian regimes? Does the threat of exit by talented individuals restrict the redistributive capacity of democratic organizations? This paper revisits that long-standing debate by analyzing the interplay between compensation structure and quit behavior in the distinct yet underexplored institutional setting of worker-managed firms. The study exploits two novel administrative data sources: a panel of Uruguayan workers employed in both worker-managed and conventional firms; and a linked employeremployee panel data set covering the population of Uruguayan worker-managed firms and their workers from January 1997 to April 2010. A key advantage of the data is that it enables one to exploit within-firm variation on wages to construct an ordinal measure of the worker ability type. The paper's four main findings are that (1) worker-managed firms redistribute in favor of low-wage workers; (2) in worker-managed firms, high-ability members are more likely than other members to exit; (3) the hazard ratio of high-ability members is lower for founding members and for those employed by worker-managed firms in which there is less pay compression; and (4) high-ability members are less likely to quit when labor market conditions in the capitalist sector are less attractive. This paper contributes to the study of the interplay between equality and incentives that permeates many debates in public finance, comparative economic systems, personnel and organizational economics.
Keywords: H00; J54; J62; M52; P0; 330; labor managed firms; redistribution; compensation structure; job mobility